ETHNOMATHEMATIC ON WALL ORNAMENTS OF LEBONG TRADITIONAL HOUSES - Rangga, Rangga Siswanto; Nyayu Masyita Ariani; Winda Ramadianti (EMTEKA: Jurnal Pendidikan Matematika, 2025)
This study aims to identify ethnomathematics found in the wall ornaments of Lebong traditional houses. This research is a qualitative descriptive research using an ethnographic approach. This research was carried out in Gunung Alam Village, Pelabai District, Lebong Regency, Bengkulu Province. The focus of this research informant is the head of the traditional and cultural leaders in Lebong district. Data collection is carried out through observation, interviews, and documentation. Observations in this study were made through direct observation of the wall ornaments of Lebong traditional houses, it was identified that there was ethnomathematics in the wall ornaments of Lebong traditional houses. Furthermore, the information is deepened with interviews and documentation. The data analysis process is carried out by means of data collection, data reduction, data presentation, and drawing conclusions. The results of this study show that in the wall ornaments of Lebong traditional houses there are ethnomathematics, namely circles, rotations, reflections and translations. Ethnomathematical activities, namely measuring, counting and designing, are found in the process of making wall ornaments. Furthermore, the findings of this research can be developed into teaching materials such as modules, LKPD, and others based on wall ornaments of Lebong traditional houses.